2003
DOI: 10.1159/000068860
|View full text |Cite
|
Sign up to set email alerts
|

Open and Laparoscopic Treatment of Nonparasitic Splenic Cysts

Abstract: Background: Nonparasitic splenic cysts are rare. Therefore, there is no ‘evidence-based’ information regarding their optimal surgical management. In the last years the laparoscopic approach has gained increasing acceptance in splenic surgery. The aim of this study is to present our experience with the laparoscopic management of splenic cysts. Methods:The medical records of 7 patients with splenic cysts were reviewed retrospectively. Results: One patient had an open partial splenic resection. Five patients, 3 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 15 publications
1
52
0
2
Order By: Relevance
“…There was no recurrence after 5 years of follow up. Several other studies have shown that laparoscopic partial cystectomy to be safe and effective (Till and Schaarschmidt, 2004;Mackenzie et al, 2004;Dan et al, 2010;Sellers and Starker, 1997;Gianom et al, 2003;Mertens et al, 2007). Results of our review support that laparoscopic partial cyst excision is safe and effective spleen preserving option in the treatment of NPSC.…”
Section: Discussionsupporting
confidence: 76%
“…There was no recurrence after 5 years of follow up. Several other studies have shown that laparoscopic partial cystectomy to be safe and effective (Till and Schaarschmidt, 2004;Mackenzie et al, 2004;Dan et al, 2010;Sellers and Starker, 1997;Gianom et al, 2003;Mertens et al, 2007). Results of our review support that laparoscopic partial cyst excision is safe and effective spleen preserving option in the treatment of NPSC.…”
Section: Discussionsupporting
confidence: 76%
“…Surgical treatment for splenic cysts is indicted when symptomatic or large than 5 cm, as spontaneous resolution is less likely [12,15,16]. Treatment goals include elimination of cysts and prevention of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…blužnies cistos, kurias paprastai sukelia cistinis echinokokas (Echinoccocus granulosus), o Vidurio Europoje ir Šiaurės Amerikoje neparazitinės cistos esti dažnesnės [2,7]. Remiantis epidemiologiniais duomenimis, didžiąją neparazitinių cistų dalį sudaro potrauminės pseudocistos [8].…”
Section: Diskusijaunclassified
“…Pasak daugelio autorių, simptominės ir/ar 5 cm dydžio ir didesnės neparazitinės blužnies cistos turėtų būti gydomos chirurginiu būdu. Tokio dydžio blužnies cistos sietinos su didesne komplikacijų -cistos plyšimo, cheminio peritonito ir pūlinio formavimosi -rizika [7,9,11,12]. Kenney ir kolegų atliktame retrospektyviniame tyrime (115 pacientų) teigiama, jog dėl itin reto neparazitinių blužnies cistų komplikacijų dažnio neoperacinė gydymo taktika priimtina visoms neparazitinėms besimptomėms blužnies cistoms, nepriklausomai nuo jų dydžio.…”
Section: Diskusijaunclassified